Prospects of foreign direct investments in technology transfer - Edyta Gherigi; Nataliya Voytovych (Economic and Environmental Studies (E&ES), 2018)
The authors investigated the impact of foreign direct investment on economically developed and developing countries, and also on transition economy countries as far as technology transfer is concerned. The results show a significant foreign direct investment influence on the economic growth of developing countries and transition economy countries. The present paper examines inflows of inward Foreign Direct Investment (FDI) during 2005-2016. There has been research conducted on the determinants of FDI inflows for developed and developing countries, but little has been done concerning this issue especially in the case of transition economies. The authors consider the possibilities the FDI inflows from investor-countries in the area of innovation and technology transfer in the years 2010-2015. In this case, Asia deserves attention. FDI allows technology transfer from developed countries to further extract surplus from the developing countries and transition countries.
Keywords: O14; Z32; 330; foreign direct investment; technology transfer; developed economies; developing economies; transition economies